A multicenter real‐life study to determine the efficacy of corticosteroids and olfactory training in improving persistent COVID‐19‐related olfactory dysfunction. Issue 1 (2nd December 2022) - Pendolino, Alfonso Luca; Ottaviano, Giancarlo; Nijim, Juman; Scarpa, Bruno; De Lucia, Giulia; Berro, Cecilia; Nicolai, Piero; Andrews, Peter J.
Abstract: Background: No definitive treatment exists to effectively restore function in patients with persistent post‐infectious olfactory dysfunction (OD). Corticosteroids have been considered as a therapeutic option in post‐infectious OD but their benefit in COVID‐19‐related OD remains unexplored. We aim to determine the role of the combination of corticosteroids plus olfactory training (OT) in improving persistent COVID‐19‐related OD. Methods: A multicenter real‐life cohort study was conducted between December 2020 and April 2022 on patients with reported COVID‐19‐related OD. Only patients with confirmed OD at Sniffin' Sticks (S'S) and those who attended their 6‐month follow‐up were included. Patients were started on a combined treatment of corticosteroids and OT. Patients refusing corticosteroids or not doing any treatment formed the control groups. Visual analogue scale (VAS) for sense of smell and SNOT‐22 were used to assess patients reported symptoms. Results: Sixty‐seven subjects with reported COVID‐19‐related OD were initially seen. Normosmic patients at S'S ( n  = 14) and those not attending their follow‐up ( n  = 9) were excluded. Of the 44 patients included in the analysis, 19 patients had the combined treatment (group A), 16 patients refused to take corticosteroids and did the OT alone (group B) whereas 9 patients did not do any treatment (group C). An improvement of threshold + discrimination + identification (TDI) score ( p  = .01) and VAS for smell ( p  = .01) was found in group A whereas only the TDI score improved in group B ( p  = .04). Presence of comorbidities, age, sex (male), and length of OD negatively influenced olfactory recovery. Conclusions: Our study confirms the importance of OT in long‐term OD suggesting that the addition of corticosteroids may give a benefit in terms of patient's perceived olfaction. Level of Evidence: 2b Abstract : No definitive treatment exists to effectively restore function in patients with persistent post‐infectious olfactory dysfunction(OD). Corticosteroids have been considered as a therapeutic option in post‐infectious OD but their benefit in COVID‐19‐related OD remains unexplored. Our study confirms the importance of OT in long‐term OD suggesting that the addition of corticosteroids may give a benefit in term of patient's perceived olfaction.